2003
DOI: 10.1017/s1074070800028212
|View full text |Cite
|
Sign up to set email alerts
|

Productivity and Economic Effects of Antibiotics Used for Growth Promotion in U.S. Pork Production

Abstract: Public health experts are concerned about the diminishing efficacy of antibiotics. Some have called for a ban on growth-promoting antibiotics in animal agriculture. This study identifies the contribution of growth-promoting antibiotics in the grower/finisher phase of U.S. pork production. With National Animal Health Monitoring System swine data, relationships are estimated between growth-promoting antibiotic use and productivity. Results indicate improvements in average daily gain (0.5%), feed conversion ratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 16 publications
1
17
0
Order By: Relevance
“…The vertical dotted line separates pre-1985 studies from more recent (post-1985) studies. Data compiled from Hays (1977), Zimmerman (1986), Dritz et al (2002), Miller et al (2003Miller et al ( , 2005, and Van Lunen (tylosin) in 4,890 healthy pigs and corroborated the trend observed by Braude et al (1953) 20 years earlier ( Figure 5). These high levels of baseline performance are mentioned in recent studies that found limited growth response to AGPs (Dritz et al 2002, Van Lunen 2003.…”
Section: Figuresupporting
confidence: 64%
See 2 more Smart Citations
“…The vertical dotted line separates pre-1985 studies from more recent (post-1985) studies. Data compiled from Hays (1977), Zimmerman (1986), Dritz et al (2002), Miller et al (2003Miller et al ( , 2005, and Van Lunen (tylosin) in 4,890 healthy pigs and corroborated the trend observed by Braude et al (1953) 20 years earlier ( Figure 5). These high levels of baseline performance are mentioned in recent studies that found limited growth response to AGPs (Dritz et al 2002, Van Lunen 2003.…”
Section: Figuresupporting
confidence: 64%
“…In another observational study, Miller et al (2003) estimated that AGP use increased average daily weight by 0.5% and feed efficiency by 1.1%-much less than the two-digit improvements reported in the 1980s (Cromwell 2002). Recent studies have mostly found a small significant growth response to AGPs for nursery pigs (Dritz et al 2002, McBride et al 2008) and small responses that were not statistically different from zero for finishing pigs (McBride et al 2008, Key & McBride 2014.…”
Section: Change In Effect Size Over Timementioning
confidence: 97%
See 1 more Smart Citation
“…However, the growth response to AGP appears to be much less important when animal nutrition, hygiene practices, as well as genetic potential and health status of animals are optimal. Indeed, recent studies (post-2000) have shown that productivity gains from AGP are lower than what was reported in earlier studies [7, 9, 10]. More specifically, Miller et al [9] reported that the use of AGP in pork production increased the average daily weight by 0.5% and feed efficiency by 1.1%; that is much less that previously reported in the 1980s [10].…”
Section: Antibiotic Use and Resistance In Poultry And Swine Productionmentioning
confidence: 90%
“…However, according to Wierup (2001), banning the use of antibiotic growth-promoters in animal feeds is often associated to an increase in both preventive and curative use of antibiotics. Probably, the better productive performance found in batches receiving only in-feed medication was due to a preventive use of antibiotics whereas water and injection medications were used more for curative purposes (Miller et al, 2003). In any case, these results show that batches treated more times with antibiotics are related to poorer health status.…”
Section: P S Agostini Et Al / Span J Agric Resmentioning
confidence: 88%